Clinical Supervision Model: Efforts to Improve the Performance of Islamic Religious Education Teachers in Indonesia - Rizki Kurniaty; Indrayuda Indrayuda (STAI Hubbulwathan Duri, 2024)
This study seeks to develop an effective clinical supervision model to enhance the performance of Islamic Religious Education (PAI) teachers in primary schools within Agam District, addressing challenges in classroom practices and improving learning quality. Using a qualitative approach with a development research design, the study began with a comprehensive needs analysis. Data were collected through interviews, observations, and document analyses involving Islamic Education teachers in Agam District. Identified needs guided the formulation of objectives for the clinical supervision model. The developed clinical supervision model is grounded in moral and ethical principles, including fairness and equality, as foundational to the supervision process. Key components of the model include supervision methods, evaluation tools, training strategies, and communication mechanisms tailored to address teachers’ challenges. By focusing on tailored supervision strategies, the model emphasizes practical support for teachers, fostering professional growth and ethical conduct. It highlights the importance of structured and supportive oversight in achieving higher teaching standards and improved classroom outcomes. The study provides an effective clinical supervision model designed to support the performance of Islamic Education teachers in Indonesia, particularly in the Agam District. The model holds the potential to significantly enhance the quality of Islamic Education by addressing practical challenges faced by teachers, ensuring better educational outcomes for primary school students.